First, combine like terms on the left side of the equation:
5m - 3m + 2 = 6m - 4
(5 - 3)m + 2 = 6m - 4
2m + 2 = 6m - 4
Next, subtract color(red)(2m) and add color(blue)(4) to each side of the equation to isolate the m term while keeping the equation balanced:
2m - color(red)(2m) + 2 + color(blue)(4) = 6m - color(red)(2m) - 4 + color(blue)(4)
0 + 6 = (6 - color(red)(2))m - 0
6 = 4m
Now, divide each side of the equation by color(red)(4) to solve for m while keeping the equation balanced:
6/color(red)(4) = (4m)/color(red)(4)
(2 xx 3)/color(red)(2 xx 2) = (color(red)(cancel(color(black)(4)))m)/cancel(color(red)(4))
(color(red)(cancel(color(black)(2))) xx 3)/color(red)(color(black)(cancel(color(red)(2))) xx 2) = m
3/2 = m
m = 3/2